Development of IoT-Based Home Security Monitoring and Management Systems to Support Smart City Ecosystems - Aldo Dwi Wahyudi; I Gede Puja Astawa; Faridatun Nadziroh (AI Society & STMIK Indonesia, 2025)
The safety of the house and its contents is an essentialneed and must be maintained to avoid unwanted things. This is because of the increasing prevalence of criminal acts of theft in houses that their owners are abandoning. Along with the development of the times and the increase in technology, a home security device is needed to obtain accurate information, where homeowners can access and get reports about the house's conditionin real-time. To overcome these problems, it is necessary to have a tool that can monitor the house's condition and inform the house's state at any time. The device used in designing this security system, namely the Esp32-Cam microcontroller,will automatically send photos to Telegram,and the buzzer alarm and LED flash will be turned on;if this thief gets closer to the front door of the house, then the ultrasonic waves will also be activated.